Learning Style, Self-Regulated Learning, and Academic Resilience: Determinants of Creative Thinking Ability in SMAN 1 Waru Students - Budianti, Tria (Journal Of Education And Teaching Learning (JETL), 2025)
The ability to think creatively is one of the main competencies that are urgently needed in the 21st century education era, especially in facing global challenges and competition in the Industrial Revolution 4.0. The study identified the influence of three main factors, namely learning style, self-regulated learning, and academic resilience on the creative thinking ability of grade XII students of SMAN 1 Waru in economics. The research uses a quantitative approach with a survey method, involving 50 students who are selected through random sampling techniques. Data collection was carried out through questionnaires to measure learning styles, self-regulated learning, and academic resilience, and essay tests to evaluate students' creative thinking skills. The results of regression analysis showed that learning style and academic resilience had a positive influence on creative thinking ability, but self-regulated learning did not show statistical significance. These results indicate the importance of a holistic approach to learning as well as collaboration between teachers, students, and the environment to optimize creative thinking in facing global challenges.